A study of the relationship between EEG and situation awareness of forklift drivers in task scenarios with different complexities. - Kang, Yutao; Tao, Yaojie; Wu, Jianjun; Jiao, Yu; Liu, Feng; Huang, Wei (International Journal of Occupational Safety & Ergonomics, 2026)
Situation awareness (SA) loss in forklift operations is a major human error source. Accurately assessing the SA levels of forklift drivers is essential. While physiological sensors such as electroencephalography (EEG) have been proposed to measure SA, the EEG–SA relationship remains unclear. This study analyzed EEG data from 11 forklift operators, comparing EEG states between high and low SA groups. Using permutation tests, the study assessed multi-band EEG correlations (F, C, P, O regions) with SA and examined how scenario complexity influenced these relationships. Results revealed distinct EEG patterns (θ, α and β waves in F, C, P and O regions) between high and low SA groups: θ / β, θ / (α + β) in the C and P regions, and θ / β, (α + θ) / (α + β) in the O region consistently correlating with SA across scenarios – and these indicators strengthened with scenario complexity. The findings advance EEG-based SA assessment, aiding accurate SA measurement in real-world settings.